COMPARISON OF TRANEXAMIC ACID SOAKED MEROCEL AND SALINE WATER SOAKED MEROCEL IN CONTROL OF EPISTAXIS - Kumar Sah, Mukesh; Jha, Amit; Mandal, Payal; Kumar Pradhan, Ram (Journal of Chitwan Medical College, 2024)
Background: Management of epistaxis usually requires nasal packing. Merocel nasal tampon is one of the commonly used materials for packing. The nasal tampon swells and fills the nasal cavity and applies pressure over the bleeding point after applying water or water based solution over it, after placing it inside the nasal cavity. Tranexemic acid (a water based solution) may have additional benefit in epistaxis control by exerting its local hemostatic effect. This study compared control rate of epistaxis after the application of tranexemic acid solution versus control rate of epistaxis after application of saline water over the merocel nasal tampon. Methods: This comparative observational study was conducted from June 2020 to December 2022 at National Medical College Teaching Hospital (NMCTH), Nepal. Seventy patients with epistaxis; 35 in tranexamic acid soaked merocel nasal pack group and 35 in saline soaked merocel nasal pack group were enrolled after informed consent. Success in control of epistaxis was compared between these two groups. Results: Successful control of epistaxis was achieved in greater number of cases in tranexemic acid soaked merocel group (85.7%) versus saline soaked merocel group (68.6%), but statistically not significant (P value 0.077). The length of hospital stay was significantly shorter in tranexemic acid group (P value 0.037). Conclusions: Merocel is an effective material used in anterior nasal packing for control of epistaxis. Tranexemic acid injection to expand the merocel pack does not provide additional advantage in control of bleeding, however, it shortens the duration of the hospital stay.